The effect of whole-body vibration and resistance training on muscle strength in a 13-year-old boy with m. biceps femoris lesion and posttraumatic calcification - Milan, Pantović; Madić, Dejan; Popović, Boris; Batez, Maja; Obradović, Jelena (Vojnosanitetski pregled, 2015)
Introduction. Skeletal muscle atrophy is a common adaptation after major muscle lesion of m. biceps femoris that results in numerous health-sport related complications. Resistance strength training and whole-body vibration (WBV) have been recognized as an effective tool, which attenuates atrophy and evokes hypertrophy. Case report. We presented a 13-year-old boy with a lesion of m. biceps femoris and post-traumatic calcification sustained in soccer training session 6 month prior participation in this study. The patient underwent training 3 times a week for 7 weeks, including unilateral progressive WBV + resistance training (RT) of the right hamstrings muscle group using WBV and weights. Hamstrings muscle strength was measured using a Cybex isokinetic dynamometer. At the end of week 4, the patient peak torque value of the involved leg increased from 39% body weight (BW) to 72% BW and bilateral deficit decreased from -64% to -35%; at the end of week 7 the participant’s peak torque value of the involved leg increased from 72% BW to 98% BW and bilateral deficit decreased from -35% to -3%, respectively. Conclusion. Unilateral WBV + RT protocol evokes strength increase in the hamstrings muscle group. This case study suggests that adding WBV, as well as the RT program have to be considered in the total management of strength disbalance. Further studies are needed to verify the efficiency of WBV + RT protocol over the classic physical therapy exercise program.